Exercice 3 :
1) f (x) = (3x + 1)² - 49
f (x) = (3x)² + 2 * 3x * 1 + 1² - 49
f (x) = 9x² + 6x + 1 - 49
f (x) = 9x² + 6x - 48
2) f (x) = (3x + 1)² - 49
f (x) = (3x + 1)² - 7²
f (x) = (3x + 1 - 7) (3x + 1 + 7)
f (x) = (3x - 6) (3x + 8)
3) a. Pour x = - 1/3
f (x) = 9x² + 6x - 48
f (x) = 9 * (- 1/3)² + 6 * (- 1/3) - 48
f (x) = 9 * 1/9 - 6/3 - 48
f (x) = 9/9 - 2 - 48
f (x) = 1 - 2 - 48
f (x) = - 49
Pour x = 2
f (x) = (3x - 6) (3x + 8)
f (x) = (3 * 2 - 6) (3 * 2 + 8)
f (x) = (6 - 6) (6 + 8)
f (x) = 0 * 14
f (x) = 0
Pour x = √5
f (x) = 9x² + 6x - 48
f (x) = 9 * (√5)² + 6 * √5 - 48
f (x) = 9 * 5 + 6√5 - 48
f (x) = 45 + 6√5 - 48
f (x) = - 3 + 6√5
b. On cherche x tel que f (x) = 0
(3x - 6) (3x + 8) = 0
D'après la règle du produit nul :
3x - 6 = 0 ou 3x + 8 = 0
3x = 6 3x = - 8
x = 6/3 x = - 8/3
x = 2
L'équation a donc deux solutions : S = {2 ; - 8/3}.
c. 9x² + 6x - 48 = 9x²
6x - 48 = 9x² - 9x²
6x - 48 = 0
6x = 48
x = 48/6
x = 8